Esophagojejunostomy after total gastrectomy for caustic injuries. Issue 2 (1st March 2014) - Chirica, M.; Kraemer, A.; Petrascu, E.; Vuarnesson, H.; Pariente, B.; Halimi, B.; Munoz-Bongrand, N.; Sarfati, E.; Cattan, P.
Summary: The objective of the study was to compare outcomes of emergency esophagogastrectomy (EGT ) and total gastrectomy with immediate esophagojejunostomy (EJ ) in patients with full-thickness caustic necrosis of the stomach and mild esophageal injuries. After caustic ingestion, optimal management of the esophageal remnant following removal of the necrotic stomach remains a matter of debate. Between 1987 and 2012, 26 patients (men 38%, median age 44 years) with isolated transmural gastric necrosis underwent EGT ( n = 14) or EJ ( n = 12). Early and long-term outcomes of both groups were compared. The groups were similar regarding age ( P = 0.66), gender (0.24), and severity of esophageal involvement. Functional success was defined as nutritional autonomy after removal of the jejunostomy and tracheotomy tubes. Emergency morbidity (67% vs. 64%, P = 0.80), mortality (17% vs. 7%, P = 0.58), and reoperation rates (25% vs.14%, P = 0.63) were similar after EJ and EGT . One patient (8%) experienced EJ leakage. One patient in the EJ group and 13 patients in the EGT group underwent esophageal reconstruction ( P < 0.0001). Aggregate in hospital length of stay was significantly longer in patients who underwent EGT (median 83 [33–201] vs. 36 [10–82] days, P = 0.001). Functional success after EJ and EGT was similar (90% vs.69%, P = 0.34). Immediate EJ can be safely performed after total gastrectomy for caustic injuries and reduces the need of further esophageal reconstruction.